Outcomes of Surgical Versus Conservative Management in Stanford Type a Aortic Dissection: A Single-Center Retrospective Study - Irina-Anca Eremia; Mihnea-Ioan-Gabriel Popa; Cătălin-Alexandru Anghel; Teodora-Adriana Stroe; Eduard-Alexandru Eremia; Andreea Nicoleta Marinescu; Remus Iulian Nica; Silvia Nica (Life)
Acute aortic dissection (AAD) is a critical cardiovascular emergency marked by the rupture of the aortic intima, resulting in blood infiltration into the media and the formation of a false lumen. AAD incidence varies by area, emphasizing the need for better diagnostics and epidemiological investigations. Bucharest University Emergency Hospital’s Emergency Department conducted this retrospective cohort analysis from May 2021 to May 2023. We examined 26 Stanford Type A aortic dissection patients to establish in-hospital mortality and one-year survival rates. The primary objective was to analyze demographic, clinical, and paraclinical factors and their impact on patient outcomes. A total of 57.7% of the study group was male and had a mean age of 58.2 years, and 69.2% of patients had hypertension, indicating its importance as a risk factor. Acute chest discomfort was reported by 53.8%, neurological problems by 30.8%, and syncope or hypotension by 42.3%. CT angiography and transthoracic echocardiogram (TTE) confirmed the diagnosis and assessed dissection severity. Pericardial effusion (19.2%) and moderate to severe aortic regurgitation (26.9%) were notable. Management varied by dissection intensity and location. Emergency surgery was performed in 61.5% of patients within 24 h of diagnosis, resulting in a 12.5% in-hospital death rate. Conservatively managed patients had a 60.0% in-hospital death rate. Timely intervention is crucial, since the surgical cohort had an 87.5% one-year survival rate compared to 30% for the conservatively managed cohort. Acute renal damage (25%), protracted mechanical ventilation (31.3%), and advanced supportive care infections were postoperative sequelae. Conservative care exacerbated visceral ischemia (20%) and heart failure (10%). Advanced age and hypotension upon admission were independent mortality predictors, emphasizing the need for early risk assessment and personalized treatment. Multimodal imaging, timely surgical referral, and excellent postoperative care improve AAD outcomes, according to this study.